STUDENTS' VIEWS ON THE IMPLEMENTATION OF PHOTOVOICE BASED ON BOARD GAME IN SPEAKING SKILL IN SENIOR HIGH SCHOOL - Nazar Hasby; Neneng Islamiah; Fitra Ramadani; Harum Mustika (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
Abstract: This research aims to determine students' views and to find out the benefits of implementation of photovoice based on board game in speaking activity in senior high school. In this research, the researcher design used qualitative research, data collection procedures were conducted through observations and interviews with students of class XII of SMAN 3 Banjarmasin, South Kalimantan province, Indonesia, with pseudonyms A, B, C, D, E, F. The researcher conducted a semi-structured interview to investigate second-semester student's views on the implementation of a board game. It can be concluded that photovoice based on board game as educational games in the classroom acts as a tremendously helpful learning media that can improve the students' engagement, performance, speaking skills, public speaking, confidence in speaking, and ability to speak English in class. It can be a tool to help the teachers do the formative assessment.